Integration of Public Service Information Systems for the Management of Non-Tax State Revenues at the Center for Radioactive Waste Technology - Handayani, Widya; Parjono, Parjono (KnE Social Sciences, 2022)
In today’s millennial era, technological developments have had a positive impact in terms of increasing convenience in all aspects of community life, business, economy and trade. Most government organizations are oriented to public services which must always be dynamic in keeping up with increasingly sophisticated technological advances, as well as increasingly complex work demands. Therefore, all ministries and institutions compete to create technological innovations that can provide convenience for partners in obtaining fast, efficient and effective public services. Public services in the central government are generally closely related to non-tax state revenue (PNBP). The Center for Radioactive Waste Technology (PTLR) is one of the institutions within BATAN that provides public services in the form of radioactive waste management services to BATAN’s stakeholders. To improve the quality of its public services, and PTLR performance as a PNBP management institution, PTLR created the E-LIRA webbased administration service application. Stakeholders can easily apply for radioactive waste management services without having to come in person so as to save costs and time. Since its launch in 2017, the E-LIRA application has been further developed by integrating several other government applications to address other problems and preferences of PTLR’s partners. The integration of E-LIRA and the SIMPONI application of the Ministry of Finance is expected to provide convenience for the revenue treasurer as an internal party in managing PNBP, as the treasurer will no longer need to issue billing to external partners who can easily print the bill and obtain valid proof of payment. Keywords: public service, E-LIRA, PNBP